Place, policy and practitioners: on rehabilitation, independence and the therapeutic landscape in the changing geography of care provision to older people in the United Kingdom - Martin, Graham P.; Nancarrow, Susan A.; Parker, Hilda; Phelps, Kay; Regen, Emma (2005)
A growing body of literature in geography and other social sciences considers the role of place in the provision of healthcare. Authors have focused on various aspects of place and care, with particular interests emerging around the role of the psychological, social and cultural aspects of place in care provision. As healthcare stretches increasingly beyond the traditional four walls of the hospital, so questions of the role of place in practices of care become ever more pertinent. In this paper, we examine the relationship between place and practice in the care and rehabilitation of older people across a range of settings, using qualitative material obtained from interviews and focus groups with nursing, care and rehabilitation staff working in hospitals, clients’ homes and other sites. By analysing their testimony on the characteristics of different settings, the aspects of place which facilitate or inhibit rehabilitation and the ways in which place mediates and is mediated by social interaction, we consider how various dimensions of place relate to the power-inscribed relationships between service users, informal carers and professionals as they negotiate the goals of the rehabilitation process. We seek to demonstrate how the physical, psychological and social meanings of place and the social processes engendered by the rehabilitation encounter interact to produce landscapes that are more or less therapeutic, considering in particular the structuring role of state policy and formal healthcare provision in this dynamic.